Endometriosis in the Anterior Abdominal Wall under Previous Cesarean Section Scar. A Case Report: Endometriosis in Rare Position - Alshahri, Talal Mohammad; Alahmad, Feras; AlQarni, Mounira; AlHarbi, Sarah (RA Journal Of Applied Research, 2023)
Introduction: Endometriosis is defined as the presence of normal endometrial mucosa (glands and stroma) abnormally implanted in locations other than the uterine cavity. Case presentation: A 34-year-old woman presented to our department with a 4-year history of a painful firm Subcutaneous nodule on the previous Caesarian section scar also she experienced flares of pain with her menstrual cycle. Clinical discussion: Scar endometriosis is a rare but well-documented condition that can occur after surgical procedures, particularly cesarean section. Diagnosis is typically made based on clinical presentation and imaging studies; treatment involves surgical excision of the affected tissue. Conclusion: The condition is characterized by the presence of endometrial tissue in surgical scars and typically presents as a painful nodule or mass.